Práticas pedagógicas nas escolas indígenas: um estudo bibliográfico de teses e dissertações na área de educação - Santos, Marcineia Vieira de Almeida (Universidade Federal de São Carlos, 2025)
Contextualized within the debate on education policies for indigenous peoples and on the principles arising from the indigenous movement, this thesis focuses on Indigenous School Education, with special attention to the pedagogical practices of indigenous basic education schools. Based on research on Indigenous School Education, at the master's and doctoral levels in the area of education, we analyze whether the pedagogical practices of indigenous schools are being implemented in a differentiated, specific, bilingual/multilingual and intercultural way, as guaranteed by Brazilian legislation to realize the right of indigenous peoples to their own learning processes. This bibliographic research mapped the theses and dissertations produced in the field of education, published between 1996 and 2020, available in the Catalog of the Coordination for the Improvement of Higher Education Personnel (Capes). Our investigation was conducted in two stages: (1) mapping the studies on Indigenous School Education; (2) conducting an in-depth analysis of studies that addressed pedagogical practices in indigenous schools – time, space, materials, and resources in the organization of pedagogical work. The analysis of studies shows that indigenous schools’ pedagogical practices have increasingly aligned with the principles of differentiation, specificity, bilingualism/multilingualism, and interculturality, particularly through teachers’ initiatives and strategies; however, these practices do not represent the entirety of the organization of pedagogical work in these schools. While this scenario can be understood as progress in the field of Indigenous School Education, significant challenges remain related to insufficient understanding and practice of intercultural dialog by the state, through its departments of education. These challenges should be addressed in order to fully guarantee indigenous peoples’ right to their own learning processes.
Pedagogical practices in indigenous schools: a bibliographic study of theses and dissertations in the field of education
Keywords: Escola indígena; Educação escolar indígena; Processos próprios de aprendizagem; Práticas pedagógicas; Indigenous schools; Indigenous school education; Indigenous peoples learning processes; Pedagogical practices; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS